Strategi Marketing Communication Mix: Studi Kasus Wisata Alam pada Desa Minggirsari Kabupaten Blitar - Wijayanti, Anita Reta Kusuma; Sari, Hesty Puspita (JURNAL SOSIAL HUMANIORA (JSH), 2023)
Following the pandemic, there has been a surge in interest in natural tourism as a means to attract travelers. Minggirsari Village, since 2019, has been actively harnessing its natural resources to entice tourists and has emerged as a trailblazing model village in Blitar Regency, successfully preserving and leveraging its natural splendors for tourism. This study endeavors to delineate Minggirsari's marketing communication strategy in promoting its natural destinations, employing the Marketing Communication Mix model. The qualitative case study methodology was employed, involving on-site observations, interviews with tourism managers, and activity documentation to gather and subsequently analyze data, following the Miles and Hubbermen theory's stages of data collection, processing, presentation, and conclusion drawing. Minggirsari Village's Nature Tourism employs a diverse marketing communications mix encompassing personal sales, advertising, promotions, and public relations to augment tourist footfall, encapsulated by the rallying cry "Ayo Dolan Nang Minggirsari" ("Let's Play in Minggirsari"). The integration of natural tourism with Minggirsari's creative economic potential, epitomized by the #ayodolankeminggirsari movement, demonstrates effective management of human resources, promotions, and auxiliary tourism facilities. Future research avenues could focus on gauging the responses of visitors to Minggirsari Village's natural tourism offerings, thereby enriching our understanding of its impact and efficacy.